Innovative Behavior: The Role of Self-Efficacy and Work Engagement of Gen Z employees - Karen Christabel Reviana; Fenika Wulani; Dominicus Wahyu Pradana (Telaah Bisnis, 2025)
This study aims to analyze the influence of self-efficacy on innovative behavior mediated by work engagement among Gen Z employees. We conducted a survey using a questionnaire distributed via Google Forms. A total of 155 responses were received from Gen Z employees in the three cities in East Java. We use SmartPLS software to analyze the data using the partial least squares–based structural equation modelling (PLS-SEM) approach. The research results indicate that self-efficacy has a significant impact on innovative behavior. Moreover, we found that work engagement mediates the relationship between self-efficacy and innovative behavior. By understanding the factors influencing the innovative behavior of Gen Z employees, companies can effectively apply human resource management. Acquiring, developing, and retaining Gen Z employees with high self-efficacy is crucial for increasing work engagement and subsequently enhancing innovative behavior